Who Increases Emergency Department Use? New Insights from the Oregon Health Insurance Experiment - Augustine Denteh; Helge Liebert (Center for Economic Studies and ifo Institute (CESifo), 2022)
We provide new insights regarding the finding that Medicaid increased emergency department (ED) use from the Oregon experiment. We find meaningful heterogeneous impacts of Medicaid on ED use using causal machine learning methods. The treatment effect distribution is widely dispersed, and the average effect is not representative of most individualized treatment effects. A small group—about 14% of participants—in the right tail of the distribution drives the overall effect. We identify priority groups with economically significant increases in ED usage based on demographics and prior utilization. Intensive margin effects are an important driver of increases in ED utilization.
Keywords: H75; I13; I38; 330; Medicaid; ED use; effect heterogeneity; causal machine learning; optimal policy